EXPLORING ENTREPRENEURIAL LEADERSHIP STRATEGIES: A COMPREHENSIVE LITERATURE REVIEW FOCUSED ON GENERATION Z IN THE DIGITAL ERA - Pramudita, Dimas Ahsan; Prawesti, Marisa Intan; Masruroh, Masruroh; Wulandari, Siti Sri; Artanti, Yessy (Universitas Nusa Cendana, 2025)
This study analyzes the entrepreneurial leadership strategies employed by Generation Z to address challenges in the digital era. As the digital business ecosystem evolves, there is an increasing demand for innovative and adaptive leaders who can effectively leverage technology. The research methodology adopts a qualitative approach through a literature review, collecting relevant journal articles and books to identify patterns and relationships within Generation Z's entrepreneurial leadership strategies. Data are analyzed using an analytical framework to determine key themes such as entrepreneurial leadership, Generation Z, and the digital era. Findings indicate that effective entrepreneurial leadership strategies for Generation Z require a comprehensive, flexible, and forward-looking approach. Successful strategies must integrate digital literacy, character education, and relevant entrepreneurship training. This research demonstrates the value of adopting an ideal approach that emphasizes three main aspects: leveraging technology as an operational foundation, fostering collaborative and supportive leadership styles, and promoting personalized human resource development. Keywords: Entrepreneurial Leadership; Generation Z; Digital Era; Strategic Leadership